Analisis Efisiensi Alokasi Dana BOS untuk Pengendalian Biaya Operasional Sekolah Dasar - Denis Bahari; Tri Reza Wibowo (proceedings.icesy, 2026)
This study examines an emergency strategy to reduce basic education costs through optimizing the utilization of the School Operational Assistance (BOS) fund, aiming to alleviate household financial burdens and ensure equitable access to education. Employing a qualitative case study approach, the research was conducted at SMP NU Darul Maghfur Al Khotiby to gain an in-depth and contextual understanding of the phenomenon. Data were collected through in-depth interviews with the principal, BOS treasurer, teachers, and parents, supplemented by participatory observation of school activities and documentation of BOS financial reports, school budget plans, and policy records. Data analysis followed the Miles & Huberman interactive model, encompassing data reduction, data display, and conclusion drawing/verification through triangulation. The findings reveal that while BOS funds positively contribute to educational qualityevidenced by improved student scores and school standardsthey have not yet significantly reduced family expenditures due to persistent hidden costs. Furthermore, the effectiveness of BOS fund management heavily depends on the principal’s managerial capacity and parental involvement. Therefore, optimizing BOS requires strengthening strategic leadership, accountability mechanisms, and multi-stakeholder collaboration to achieve both cost equity and quality in education.